Wound Healing Activity of Ethanolic Extract Gel of Tawas Ut Tuber (Ampelocissus rubiginosa L.) in Incisional Model Wistar Rats - Khoerul Anwar; Dewita Fitri Widodo; Nurlely Nurlely; Liling Triyasmono; Sudarsono Sudarsono; Agung Endro Nugroho (Majalah Obat Tradisional, 2018)
Tawas ut tuber (Ampelocissus rubiginosa Lauterb.) is empirically used in wound healing by Dayak community. The present study was undertaken to assess wound healing activity of gel from ethanol extract of A. rubiginosa tuber using parameters of the closure of wound length, tensile strength, and histopathological observations. This study used twenty-five male Wistar rats divided into five groups: positive control (Bioplacenton®), negative control (placebo gel), and three of testing groups with gel extract (concentrations of 1.5%, 2.0%, and 2.5%). Wound healing activity was evaluated to 4 cm length and ± 2 mm depth incision wound model on the back skin of rats. The measurement of wound length was observed on the day of 4th, 8th, 12th, 16th, and 20th used quantitative analyze. On the day of 20th, animal was anaesthetized and the skin has been taken for tensile strength evaluation and histopathological observations. This study showed that group treated with gel extract at the concentration of 2.5% experienced higher wound healing activity with average percentage of wound closure of 99.00% ± 0.16, tensile strength 3.8541 gram/mm2, and proved with the re-epithelization, neocapillarization, and increase collagen density appeared in histopathological observations. Based on this study, gel from ethanol extract of A. rubiginosa tuber possesses wound healing activity.